Cover Feature: Halogen Complexes of Anionic N‐Heterocyclic Carbenes (Chem. Eur. J. 13/2021). Issue 13 (7th January 2021) - Frosch, Jenni; Koneczny, Marvin; Bannenberg, Thomas; Tamm, Matthias
Abstract : Iodine complexes of anionic N‐heterocyclic carbenes (NHC) act as electrophiles towards a variety of nucleophiles, with the interactions ranging from noncovalent charge‐transfer or halogen bonding to covalent 3‐center, 4‐electron bonding. Hypervalent (10‐X‐2) bis(carbene)iodine(I) and ‐bromine(I) complexes could be isolated and structurally characterized, and computational studies reveal that London dispersion involving the bulky NHC ligands (R=Dipp, Mes) contributes significantly to the stability of these systems. More information can be found in the Full Paper by M. Tamm et al. on page 4349 .